Zadie Smith and postcolonial trauma decolonising trauma, decolonising selves - Pérez Zapata, Beatriz (Routledge studies in contemporary literature, 2021)
This monograph analyses Zadie Smith’s White Teeth, On Beauty, NW, The Embassy of Cambodia, and Swing Time as trauma fictions that reveal the social, cultural, historical, and political facets of trauma. Starting with Smith’s humorous critique of psychoanalysis and her definition of original trauma, this volume explores Smith’s challenge of Western theories of trauma and coping, and how her narratives expose the insidiousness of (post)colonial suffering and unbelonging. This book then explores transgenerational trauma, the tensions between remembering and forgetting, multidirectional memory, and the possibilities of the ambiguities and contradictions of the postcolonial and diasporic characters Smith depicts. This analysis discloses Smith’s effort to ethically redefine trauma theory from a postcolonial and decolonial standpoint, reiterates the need to acknowledge and work through colonial histories and postcolonial forms of oppression, and critically reflects on our roles as witnesses of suffering in global times